2023
DOI: 10.9734/ijpss/2023/v35i203829
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Storability of Hand-hauled and Machine-hauled Sunnhemp Seeds (Crotolaria juncea Linn.)

P. Masilamani,
M. Govindaraj,
V. Alex Albert
et al.

Abstract: Aim: The present investigation is an attempt to study the effect of different harvesting and threshing methods on storability of sunnhemp seed. Study Design: Factorial Completely Randomized Design (FCRD). Place and Duration of Study: Agricultural Engineering College and Research Institute, TNAU, Kumulur, Tiruchirappalli, Tamil Nadu. Methodology: The sunnhemp seed crop was harvested and threshed using four different methods viz., manual harvesting and manual threshing, manual harvesting and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Large quantities of drymatter will add to the soil and help to increase soil physical properties and it also add nitrogen to the soil. Divya Bhayal et al [3] reported that the demand for sunhemp seed is increasing because of its potential benefits as green manure [4,5]. The availability of organic sources was reduced due to reduction in draft animals and also due to conversion of crop residues into organic matter.…”
Section: Introductionmentioning
confidence: 99%
“…Large quantities of drymatter will add to the soil and help to increase soil physical properties and it also add nitrogen to the soil. Divya Bhayal et al [3] reported that the demand for sunhemp seed is increasing because of its potential benefits as green manure [4,5]. The availability of organic sources was reduced due to reduction in draft animals and also due to conversion of crop residues into organic matter.…”
Section: Introductionmentioning
confidence: 99%